Morphometrical analysis of the coronary arteries in human fetuses (Research, Society and Development, 2021)
Coronary arteries anatomical variations in humans have presented great clinical interest for resulting in a better understanding of cardiac pathological processes. This study aimed to analyze the morphometry of the coronary arteries of human cadavers from the fourth to the ninth month of intrauterine life. A total of 62 hearts from formalin-fixed Brazilian fetuses, with gestational ages ranging from 16 to 36 weeks, equally distributed as to gender and fetal age in each group, were analyzed. The dissection procedure was performed by removing the heart with the lungs in “monoblocks”. The length of the arteries under study was determined using a flexible tape placed along the vessels and later measured with a pachymeter. Additionally, histological analysis of the coronary artery tissues was performed to quantify the elastic fibers. The data were analyzed through two-way ANOVA, followed by Student-Newman-Keuls post hoc analysis, considering p < 0.05. When comparing the length of the right coronary artery (RCA) in fetuses between the second and third trimester a statistically significant difference was found for both males (p = 0.04) and females (p = 0.04). No statistically significant difference was found when comparing the left coronary artery (LCA) length between second and third trimester in male (p = 0.07) and female (p = 0.09) fetuses. We noticed a similar growth pattern between male and female fetuses and early development of LCA in relation to RCA.